The Role of Low-Density Lipoprotein Receptor-Related Protein 1 in Lipid Metabolism, Glucose Homeostasis and Inflammation - Actis Dato, Virginia (2018)
Metabolic syndrome (MetS) is a highly prevalent disorder which can be used to identify individuals with a higher risk for cardiovascular disease and type 2 diabetes. This metabolic syndrome is characterized by a combination of physiological, metabolic, and molecular alterations such as insulin resistance, dyslipidemia, and central obesity. The low-density lipoprotein receptor-related protein 1 (LRP1—A member of the LDL receptor family) is an endocytic and signaling receptor that is expressed in several tissues. It is involved in the clearance of chylomicron remnants from circulation, and has been demonstrated to play a key role in the lipid metabolism at the hepatic level. Recent studies have shown that LRP1 is involved in insulin receptor (IR) trafficking and intracellular signaling activity, which have an impact on the regulation of glucose homeostasis in adipocytes, muscle cells, and brain. In addition, LRP1 has the potential to inhibit or sustain inflammation in macrophages, depending on its cellular expression, as well as the presence of particular types of ligands in the extracellular microenvironment. In this review, we summarize existing perspectives and the latest innovations concerning the role of tissue-specific LRP1 in lipoprotein and glucose metabolism, and examine its ability to mediate inflammatory processes related to MetS and atherosclerosis.